Serotonin and circadian rhythms - de Pontes, André Luiz Bezerra; Engelberth, Rovena Clara Galvão Januário; da silva Nascimento Jr., Expedito; Cavalcante, Judney Cley; de Oliveira Costa, Miriam Stela Maris; Pinato, Luciana; de Toledo, Claudio Antonio Barbosa; de Souza Cavalcante, Jeferson (My University, 2010)
All mammal behaviors and functions exhibit synchronization with environmental rhythms. This is accomplished through an internal mechanism that generates and modulates biological rhythms. The circadian timing system, responsible for this process, is formed by connected neural structures. Pathways receive and transmit environmental cues to the central oscillator, the hypothalamic suprachiasmatic nucleus, which mediates physiological and behavioral alterations. The suprachiasmatic nucleus has three major inputs: The retinohypothalamic tract (a direct projection from the retina), the geniculohypothalamic tract (an indirect photic projection originating in the intergeniculate leaflet), and a dense serotonergic plexus from the raphe nuclei. The serotonergic pathway, a source of non-photic cues to the suprachiasmatic nucleus, modulates its activity. The importance of raphe nuclei in circadian rhythms, especially in photic responses, has been demonstrated in many studies. Serotonin is the raphe neurotransmitter that triggers phase shifts, inhibits light-induced phase-shifts, and plays a role in controlling the sleep-wake cycle. All data to date have demonstrated the importance of the raphe, through serotonergic afferents, in adjusting circadian rhythms and must therefore be considered a component of the circadian timing system. The aim of this paper is to review the literature addressing the involvement of serotonin in the modulation of circadian rhythm. © 2010.
Keywords: Circadian rhythm; Circadian timing system; Raphe; Serotonin; Suprachiasmatic nucleus